Ragam Hias Sulaman Benang Lame pada Tabia Pelaminan di Naras Hilir, Pariaman - Agustin, Jasmar Ruli; Pebriyeni, Eliya (Lembaga Yasin AlSys, 2025)
This study aims to describe the forms of motifs, motif names, and techniques involved in the creation of sulaman benang lame (lame thread embroidery) on tabia pelaminan in Naras Hilir, Pariaman. Sulaman benang lame is a traditional Minangkabau textile craft with high aesthetic value, serving as a central decorative element in traditional wedding platforms. The research employed a qualitative approach with a descriptive method. Data were collected through direct observation, in-depth interviews with local artisans, and visual documentation of the production process. The findings reveal that the embroidery motifs are predominantly floral, including jasmine flowers, leaves, and pucuk rebung (bamboo shoots), alongside geometric patterns such as lines and triangles. Faunal motifs, such as peacocks, are used only upon request. The embroidery technique has evolved from hand embroidery to machine embroidery, while still maintaining traditional values and local aesthetics. The production process includes designing the motif, applying lame material onto satin fabric, stitching using an embroidery machine, and cutting the outer edges of the motif to emphasize the final form. The study concludes that sulaman benang lame on tabia pelaminan represents a cultural heritage that must be preserved as a visual identity of the Minangkabau people amid the challenges of modernization.